Post traumatic retinal injuries: Does the ocular protective reflex play a crucial role?. (October 2019) - Pujari, Amar; Chawla, Rohan; Selvan, Harathy; Mukhija, Ritika; Kumar, Atul
Abstract: Traumatic retinal injuries are commonly encountered in most retinal subspecialty clinics. Retinal dialysis, detachment and other complications consequent to blunt trauma are often thought to be due to equatorial expansion of the globe following an antero-posterior compressive force. However, stretching of the globe along the primary anatomical equator may not hold true for the adjusted globe position as a consequence of the protective Bell's phenomenon which gets activated before impact. The upward and outward rolling of the globe likely creates a new equator, with the compressive forces acting along this new plane, thereby leading to stretching along the ocular coats closer to the retinal periphery. Additionally, the coup and countercoup mechanisms with increased vulnerability of temporal sclera predisposes to retinal complications more commonly along the temporal and the nasal retina. Further, retinal complications involving other quadrants can also be explained through understanding of the Bell's phenomenon.